Inside Local Governance: How Well Is Debt Managed? - Errais, Eymen (International Journal of Economics and Financial Issues, 2019)
Several debates and concerns about local elections focus on whether local governance can take root in an environment where people have a very low trust in their rulers, and deliver the economic goods: a higher rate of investment, more growth and more jobs. In this paper we aim to understand whether local authorities have the financial means and management skills to face these challenges. More specifically, we address the issue of local debt management and propose a scoring system that rates municipalities’ credit quality. Our methodology is based on a mix of quantitative modeling and qualitative analysis. Our data set incorporates all the 264 Tunisian Municipalities and spans a period over 7 years (2010-2016). Our results show that the main quantitative factor predicting good debt management is Net Cash Flow. The model shows strong efficiency and reliable predictive power. Keywords: Local governance, default risk, debt management, credit risk factors JEL Classifications: F30, G28, C50 DOI: https://doi.org/10.32479/ijefi.7486